Circle of gold - Boyd, Candy Dawson (New York : Scholastic, 1984)
Ten-year-old Mattie copes with the loss of her father and her mixed feelings towards her mother who is under pressure to support the family.
"An Apple paperback.".
Booklist.
5.1
5-8
Keywords: African Americans -- Fiction; Mothers and daughters -- Fiction; Single-parent family -- Fiction; African Americans -- Fiction; Babysitters -- Fiction; Daughters -- Fiction; Death -- Fiction